Maksimalisasi Peran Hukum Perdata Internasional Sebagai Sistem Hukum Eksternal dalam Perekonomian - Bagaskara, Rayhan Akbar; Ansari, Teuku Syahrul (Peneliti.net, 2024)
The provisions in Articles 16, 17, and 18 of the regulation concerning international private law were outdated concerning the progress and legal needs for globalization and economic development. Moreover, universal standards of international private law must be aligned with the regulations in areas such as investment law, information and electronic transaction law, and arbitration law. The urgent legislation addressing international private law tackled two main issues. To materialize this concept, the President and the House of Representatives would incorporate a draft of international private law into the 2019–2024 national legislative agenda.